Effective Science Learning: A Comparative Study between Indonesia and Finland - Fitri, Rahmadhani; Ananda, Azwar; Gistituati, Nurhizrah; Rusdinal, Rusdinal (Bioeducation Journal, 2024)
Science studies nature systematically through observation and experimentation to understand the causal relationships of natural events. Science learning not only focuses on the mastery of knowledge but also on the process of discovery, skills development, and scientific attitudes. The main challenge in science learning in Indonesia is the disparity of educational facilities between schools causing a gap in the quality of education, low science literacy of students and misconceptions. Science learning in Finland, known for its phenomenon-based and student-centered approach, offers a potential solution. The Finnish education system emphasizes interdisciplinary understanding and real-world relevance, which can be applied in Indonesia to improve the quality of science learning. This research is a literature study that identifies, evaluates and analyzes articles related to science learning in Indonesia and Finland. Results show that the adoption of Finnish methods can improve science learning in Indonesia by emphasizing hands-on experience and active student interaction. The Finnish government also supports science learning from an early age to develop children's potential. This study suggests improving education facilities and adopting best practices from Finland to improve the science education system in Indonesia.